The Benefits Associated With ISO 14001 Certification For Construction Firms: Turkish Case - TÜRK, AHMET MURAT (Elsevier Sci Ltd, The Boulevard, Langford Lane, Kidlington, Oxford Ox5 1Gb, Oxon, England, 2009)
Construction firms all over the world are increasingly seeking to obtain ISO 14001. The rapid growth in the number of ISO 14001 applications in Turkey and the share from the construction sector in this number, as a leading sector, is rather striking. This paper, using a structured questionnaire survey, investigates whether there is any dependence or relation between construction firms characteristics and having ISO 14001 certification and any difference in the perceptions related to ISO 14001 by considering both firm characteristics and two different groups as certified and non-certified firms. Additionally, it examines the perceived benefits of having ISO 14001 for certified construction firms. According to the results of analysis, although there is not any difference in perceptions on ISO 14001 certification in terms of firm characteristics and being as certified and non-certified and their both positive opinions about ISO 14001 certification. There is a relation between firms characteristics and having ISO 14001 certification. ISO 14001 certification contributes to construction firms not only in terms of environmental benefits but also with corporate management and marketing effects, thus verifying that the ISO 14001 has a positive impact on the Turkish construction sector. (C) 2008 Elsevier Ltd. All rights reserved.
Keywords: ISO 14001; Environmental management system (EMS); Construction firms; Turkey; environmental-management systems; Certification; Çevre yönetim sistemi; İnşaat firmaları; Türkiye; çevre yönetim sistemleri; belgeleme